Online recognition system for handwritten Arabic mathematical symbols - Abuzaraida, Mustafa Ali; Zeki, Akram M.; M. Zeki, Ahmed (2013)
Same as Arabic scripts, Arabic mathematical symbols have some differences with Latin mathematical symbols shape. Although, Arabic Mathematical symbols follow Latin mathematical from the structure of writing the symbols, Arabic symbols have special shape like writing direction, cursive style, and written by Arabic characters. In fact, these symbols are being used in schools and high education level around many Arabic countries. However, recently digital tablets are used rapidly for teaching in high schools in many countries. For that, there become a necessity of having an education platform to deal with Arabic scripts in general and mathematical symbols in particular. In this paper an online system for recognizing handwritten Arabic mathematical symbols is presented. The paper illustrates each phase of the system in details. The system is dealing with some Arabic mathematical symbols as initial study and to be updated with more symbols later.